1999
DOI: 10.12968/hosp.1999.60.3.1085
|View full text |Cite
|
Sign up to set email alerts
|

Surgical training for the next millennium

Abstract: The Calman reforms in training have meant that surgical training now consists of a 2-year basic training period followed by a 6-year period of higher surgical training. This article addresses the problems faced by the new Calman surgical trainees and proposes some new measures which could be introduced for surgical training in the next millennium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…6 It has been demonstrated that specialist registrars have felt the benefits of these changes within a single deanery, 4 although this is not a finding common in the surgical specialities. [7][8][9][10] Our data suggest a very marked variation in the delivery of basic education within a single speciality in the UK in contrast to the conclusions of Paice et al 4 This is particularly evident in the setting of educational objectives, feedback and the delivery of hands-on experience, three of the four cornerstones of Calman's recommendations.…”
Section: Discussionmentioning
confidence: 69%
“…6 It has been demonstrated that specialist registrars have felt the benefits of these changes within a single deanery, 4 although this is not a finding common in the surgical specialities. [7][8][9][10] Our data suggest a very marked variation in the delivery of basic education within a single speciality in the UK in contrast to the conclusions of Paice et al 4 This is particularly evident in the setting of educational objectives, feedback and the delivery of hands-on experience, three of the four cornerstones of Calman's recommendations.…”
Section: Discussionmentioning
confidence: 69%
“…I t is increasingly recognised that maintaining surgical training at a sufficient level is demanding, [1][2][3][4] particularly in more recent years, where training has been shortened, and weekly working hours decreased. 5 6 Moreover, the tendency towards increasing subspecialisation makes it difficult for many units to offer a broad spectrum of general surgical procedures to trainees, and many of the procedures performed are often done by consultants due to the high specialisation required.…”
mentioning
confidence: 99%